Extrafine triple therapy in patients with asthma and persistent airflow limitation. Issue 3 (24th September 2020) - Singh, Dave; Virchow, Johann Christian; Canonica, Giorgio Walter; Vele, Andrea; Kots, Maxim; Georges, George; Papi, Alberto
The addition of a long-acting muscarinic antagonist (LAMA) is a recognised treatment option for patients whose asthma is uncontrolled with an inhaled corticosteroid (ICS) plus long-acting β2 -agonist (LABA) combination [1]. The data supporting this recommendation were provided from studies in which the LAMA tiotropium was added to ICS/LABA combinations using separate inhalers [2, 3]. The use of separate inhalers, most often of different design, with contrasting instructions for use and dosing regimens is not only inconvenient for patients and healthcare providers who provide instruction on correct inhaler use but can also negatively impact treatment adherence and persistence and, therefore, outcomes [4–7]. These post hoc analyses suggest that extrafine triple therapy with beclometasone dipropionate, formoterol fumarate and glycopyrronium may be particularly beneficial in the phenotype of patients with asthma and persistent airflow limitation https://bit.ly/2y3XsvJ